Synergy Between Pseudomonas aeruginosa Filtrates And Voriconazole Against Aspergillus fumigatus Biofilm Is Less for Mucoid Isolates From Persons With Cystic Fibrosis - Sass, Gabriele; Marsh, Julianne J.; Shrestha, Pallabi; Sabino, Raquel; Stevens, David A. (Frontiers in Cellular and Infection Microbiology, 2022)
Persons with cystic fibrosis (CF) frequently suffer from Pseudomonas aeruginosa and Aspergillus fumigatus co-infections. There is evidence that co-infections with these interacting pathogens cause airway inflammation and aggravate deterioration of lung function. We recently showed that P. aeruginosa laboratory isolates synergistically interact with the anti-fungal azole voriconazole (VCZ), inhibiting biofilm metabolism of several A. fumigatus laboratory strains. Interaction was usually mediated via pyoverdine, but also via pyocyanin or pyochelin. Here we used planktonic filtrates of 7 mucoid and 9 non-mucoid P. aeruginosa isolates from CF patients, as well as 8 isolates without CF origin, and found that all of these isolates interacted with VCZ synergistically at their IC50 as well as higher dilutions. CF mucoid isolates showed the weakest interactive effects. Four non-mucoid P. aeruginosa CF isolates produced no or very low levels of pyoverdine and did not reach an IC50 against forming A. fumigatus biofilm; interaction with VCZ still was synergistic. A VCZ-resistant A. fumigatus strain showed the same level of susceptibility for P. aeruginosa anti-fungal activity as a VCZ-susceptible reference strain. Filtrates of most Pseudomonas isolates were able to increase anti-fungal activity of VCZ on a susceptible A. fumigatus strain. This was also possible for the VCZ-resistant strain. In summary these data show that clinical P. aeruginosa isolates, at varying degrees, synergistically interact with VCZ, and that pyoverdine is not the only molecule responsible. These data also strengthen the idea that during co-infections of A. fumigatus and P. aeruginosa lower concentrations of VCZ might be sufficient to control fungal growth.